Otentisitas dan Keterbatasan Sumber Tafsīr bi al-Maʾṯūr dalam Menangani Tantangan Pemikiran Kontemporer - Al Faruq, Abdul Qudus; Fuady, Muhammad Azhar; Jauharoh, Indi Aula; Bachtiar, Maulana Yusuf; Hasyim, Muh. Fathoni (Islamic Religious Education Departement, 2025)
This study examines the authenticity and limitations sources of Tafsīr bi al-Maʾṯūr in addressing contemporary intellectual challenges. While often regarded as authoritative for relying on the Qur'an, Hadith, and the sayings of the Sahabah and Tābi'īn, Tafsīr bi al-Maʾṯūr faces challenges such as the inclusion of Isrāiliyāt, omitted Sanad (chains of transmission), as fabricated reports. This study explores traditional scholars' approaches to these issues using qualitative and descriptive methods based on library research. It evaluates the contribution ofTafsīr bi al-Maʾṯūr to modern Islamic thought. The conclusion indicates that not all Tafsīr bi al-Maʾṯūr maintain high authenticity despite its general perception as being based on reliable sources. Some interpretations rely on narratives that lack a direct connection to the Qur'anic text, including Isrāiliyāt and fabricated hadiths, or omit Sanad, raising doubts about their credibility. Therefore, looking at previous studies which say that Tafsīr bi al-Maʾṯūr is sufficient as the primary reference in understanding the text of the Qur'an, this is fatal because a more dynamic and contextual interpretation approach is still needed to ensure that the interpretation of the Qur'an remains relevant in the modern era.